A New Nonenzymatic Method and Device to Obtain a Fat Tissue Derivative Highly Enriched in Pericyte-Like Elements by Mild Mechanical Forces from Human Lipoaspirates. Issue 11 (November 2013) - Bianchi, Francesca; Maioli, Margherita; Leonardi, Erika; Olivi, Elena; Pasquinelli, Gianandrea; Valente, Sabrina; Mendez, Armando J.; Ricordi, Camillo; Raffaini, Mirco; Tremolada, Carlo; Ventura, Carlo
Adipose tissue contains multipotent elements with phenotypic and gene expression profiles similar to human mesenchymal stem cells (hMSCs) and pericytes. The chance of clinical translation of the multilineage potential of these cells is delayed by the poor/negligible cell survival within cryopreserved lipoaspirates, the difficulty of ex vivo expansion, and the complexity of current Good Manufacturing Practice (cGMP) requirements for expanded cells. Hence, availability of a minimally manipulated, autologous, hMSC/pericyte-enriched fat product would have remarkable biomedical and clinical relevance. Here, we present an innovative system, named Lipogems, providing a nonexpanded, ready-to-use fat product. The system uses mild mechanical forces in a completely closed system, avoiding enzymes, additives, and other manipulations. Differently from unprocessed lipoaspirate, the nonexpanded Lipogems product encompasses a remarkably preserved vascular stroma with slit-like capillaries wedged between adipocytes and stromal stalks containing vascular channels with evident lumina. Immunohistochemistry revealed that Lipogems stromal vascular tissue included abundant cells with pericyte/hMSC identity. Flow cytometry analysis of nonexpanded, collagenase-treated Lipogems product showed that it was comprised with a significantly higher percentage of mature pericytes and hMSCs, and lower amount of hematopoietic elements, than enzymatically digested lipoaspirates. Differently from the lipoaspirate, the distinctive traits of freshly isolated Lipogems product were not altered by cryopreservation. Noteworthy, the features of fresh product were retained in the Lipogems product obtained from human cadavers, paving the way to an off-the-shelf strategy for reconstructive procedures and regenerative medicine. When placed in tissue culture medium, the Lipogems product yielded a highly homogeneous adipose tissue-derived hMSC population, exhibiting features of hMSCs isolated from other sources, including the classical commitment to osteogenic, chondrogenic, and adipogenic lineages. Moreover, the transcription of vasculogenic genes in Lipogems-derived adipose tissue hMSCs was enhanced at a significantly greater extent by a mixture of natural provasculogenic molecules, when compared to hMSCs isolated from enzymatically digested lipoaspirates.